Marketing : making the future happen - Corkindale, David; Balan, Peter; Rowe, Caroline (South Melbourne : Nelson, 1996)
This book is about: Understanding customers and client; Getting the complete "Match" right; The galaxy marketing implementation process; Setting prices and terms; ...
Keywords: Marketing; Management; Marketing; Marketing -- Management